Commercial special bread: Evaluation of texture, color, moisture content, water activity and nutritional labeling - Macedo Guimarães, Rafaiane; Costa, Lílian Moreira; Resende, Osvaldo; Buranelo Egea, Mariana; Takeuchi, Katiuchia Pereira (Revista Brasileira de Agrotecnologia, 2021)
Three types of special bread (WB: bread with whole-wheat flour, LWB: ‘light’ bread with whole-wheat flour, and MB: bread with multi-cereals) were purchased in the local market, and moisture content was analyzed as well as the following parameters water activity (aw), instrumental texture, and instrumental color of the bread (crust and crumb) using spectrophotometer with CIELab system (n=10). The chroma or C * value and the hue angle were also calculated. The labels of the bread were analyzed according to Resolution-RDC nº 360, which provides information about nutritional labeling of packaged foods. The three breads presented in their composition whole wheat flour and wheat fiber, which are indispensable ingredients for the loaves to be considered "special bread". The compression force applied to cause disruption in the bread was higher in WB (3.88 N) without significant difference with MB (3.79 N) and lower in LWB (2.85 N). The color parameters of the breads showed that WB was darker (lower value of L * = 34.44 in the crust) than the others.